Effects Of Led On The Micropropagation And Callus Induction Of Zingiber Officinale Var. Rubrum - Gnasekaran, Pavallekoodi (2021)
Micropropagation of medicinally important Zingiber officinale var. rubrum will generate infinite disease-free in vitro clones for plantation; preventing reservation of seed rhizome from harvest. Hence, the applicability of light-emitting diodes (LEDs) was determined for the micropropagation of Zingiber officinale var. rubrum.